PENGARUH LEVERAGE, PROFITABILITAS, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN SUB SEKTOR KONSTRUKSI DAN BANGUNAN TAHUN 2015-2019 - Kathleen Kathleen (Parsimonia - Jurnal Ekonomi dan Bisnis, 2021)
This study aims to examine the effect of leverage, profitability, and liquidity on firm value in construction and building sub-sector companies listed on the Indonesia Stock Exchange from 2015 to 2019. The number of data in accordance with the sample criteria is 50 data. This study uses multiple linear regression analysis to test the effect of each variable. The results of this study indicate that the liquidity of a company has a positive effect on firm value. This happens because the higher the liquidity ratio, the higher the company's ability to fulfill its liabilities. Companies that have a high level of liquidity are considered to have good prospects for investors to invest. Liquidity shows the funds available to pay dividends, company operations, and investments so that investors' perceptions of company performance are getting better. Leverage has no effect on firm value because investors need more information about the use of debt as company capital and consider other factors in making investment decisions. The profitability of a company also has no effect on firm value. This is due to the management's performance that does not have the ability to use the assets owned which causes net income to be small, while the assets owned by the company are very large. Theoretically, this study does not support pecking order theory because a firm's funding decisions have no effect on firm value. This is evidenced by the leverage in this study which has no effect on firm value. Meanwhile, in practical terms, companies can increase liquidity so that investors are interested, so as to increase the value of the company. However, companies must also pay attention to other factors within the company that can increase company value.